Motivations for COVID-19 vaccination: fear, solidarity, obedience, leisure orientation or thoughtlessness? - Wüstner, Kerstin (International Journal of Research in Medical Sciences, 2022)
Background: The COVID-19 pandemic exemplifies why it is important to understand people’s health behavior, and with respect to vaccination why they decided for or against it. Methods: This paper presents results of a small online-study carried out in Germany (n=281). It analyzes motivations for vaccination, including intrinsic, extrinsic, structural motivators that can be health related or not. Further, thoughtless decisions are included as well. Results: The most important aim of vaccination was to get back to normal. Social motivators were second most important. Further motivators were intrinsic, especially fear of the virus, or structural, e.g., reflecting leisure orientation. Some were motivated to get vaccinated because other people said they should. However, a remarkable number of respondents stated they got vaccinated without big thoughts. Conclusions: This small study exemplarily illustrates that various motives can influence an important health decision, such as for (or against) COVID-19 vaccination. A subgroup represents the ideal of a modern empowered citizen only to a limited extent. Health policy needs to strengthen critical health literacy of citizens even in crises.